FEATURES OF MORPHOLOGICAL CHANGES IN THE SALIVARY GLANDS OF RATS UNDER MONOSODIUM GLUTAMATE-INDUCED OBESITY - Гордієнко, Л.П.; Єрошенко, Г.А.; Непорада, К.С. (World of Medicine and Biology, 2015)
Obesity is currently regarded as pandemic. According to the literature, obesity and associated pathological conditions lead to a decrease in proper functioning of the salivary glands, and as a consequence to reduction of salivation, increased saliva viscosity and dry mouth. Mulfunctions of the salivary glands are the cause of pathological processes in the organs of the oral cavity and disruption of digestive processes in the other parts of the gastrointestinal tract. However, pathological mechanisms involved in the impact of obesity on salivary glands are not fully established.The aim of the research was to study the morphological changes in the submandibular salivary glands of rats under monosodium glutamate-induced obesity.The study was carried out on 20 rats that were divided on 2 groups. Group I was intact control (4-month old rats). Newborn rats of Group II were administered with monosodium glutamate at a dose 4 mg/g of body weight subcutaneously on the second, fourth, sixth, eighth and tenth day of life. Four-month-aged animals were sacrificed. Body Mass Index (BMI) was calculated, visceral fat was removed and weighed. Morphological studies were performed to evaluate the pathological changes in the salivary glands under glutamate-induced obesity. After 4 months in animals injected with MSG, BMI was significantly higher in comparison with control animals. The mass of visceral fat was significantly higher compared with control animals. The calculation of BMI and visceral fat accumulation suggested the development of obesity in group II.It was found that under monosodium glutamate-induced- obesity the lobed structure of salivary glands was preserved. It was established that among the end sections of epithelial cells there were epithelial cells with normal structural organization and degenerative changes. Pathomorphological changes in the connective tissue showed signs of mucoid swelling. It was found the increasing in the volume of stroma compared with the control that manifested by interlobular thickening of ductal membranes and connective tissue. Basement membrane of the ducts was irregular, epithelial ducts were deformed, flattened laterally, cytoplasm had unstructured form, irregularly shaped nuclei with condensed chromatin mainly.There was increased number of hypertrophic collagen fibers and hyperhydration of amorphous substance in periductal interstitium and interlobular connective tissue. Arterioles were spasmodic. Venules were dilated with thinning of their walls, red blood cells densely filled gap.Thus, under glutamate-induced obesity there are pathological changes in the tissues of the salivary glands such as degenerative changes of end sections of epithelial cells, deformation of ductal epithelial cells, mucoid swelling, increase in the stroma, venous congestion.
Keywords: salivary glands; obesity; monosodium glutamate